THE IMPLEMENTATION OF TEACHING ENGLISH THROUGH DISTANCE LEARNING DURING COVID-19 PANDEMIC: A CASE STUDY IN MAFAZA INTEGRATED SMART SCHOOL (MISS) NATIONAL PLUS ELEMENTARY SCHOOL MALANG - Asfiyatus Sophia (Language-Edu, 2021)
Covid-19 pandemic has made all activities of the community very limited. Teaching and learning activities in schools must also be carried out by distance learning. Thus, this research aims to dig deeper information about how distance learning of English is carried out at MISS National Plus Elementary School Malang. In addition, researchers are also looking for supporting factors and inhibiting factors for the implementation of teaching and learning English through distance learning during Covid-19 pandemic. This research is a case study conducted at MISS National Plus Elementary School Malang with a qualitative research design. This is due to the MISS National Plus Elementary School is a elementary school level which use dual curriculum, those are K13 and Cambridge Curriculum. So, English is the everyday language used in schools in formal or informal contexts. The subject of this research is a grade 1 English teacher. Qualitative research instrument is the researcher himself because the researcher has full authority in collecting and analyzing data. So that, researcher collects the data trhough observation and interview. The result of this research is a description of how the implementation of English teaching through distance learning at MISS National Plus Elementary School, supporting factors and inhibiting factors for the implementation of these activities.Keywords: Covid-19 Pandemic, Teaching English as Foreign Language, Distance Learning